2018
DOI: 10.1103/physreva.98.013841
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the signal-to-noise ratio of biphoton distribution measurements

Abstract: Single-photon-sensitive cameras can now be used as massively parallel coincidence counters for entangled photon pairs. This enables measurement of biphoton joint probability distributions with orders-of-magnitude greater dimensionality and faster acquisition speeds than traditional raster scanning of point detectors; to date, however, there has been no general formula available to optimize data collection. Here we analyze the dependence of such measurements on count rate, detector noise properties, and thresho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…The peak value is proportional to the mean value of an intensity correlation image measured in the same conditons (i.e.signal of the SNR). The standard deviation of noise in the pixels surrounding the peak is proportional to the standard deviation of the noise in an intensity correlation image acquired in the same condi- [55] shows that the SNR varies as 1{xI cl y.…”
Section: Details About the Quantum Holographic Measurements Performed In The Presence Of Static And Dynamic Stray Lightmentioning
confidence: 96%
See 2 more Smart Citations
“…The peak value is proportional to the mean value of an intensity correlation image measured in the same conditons (i.e.signal of the SNR). The standard deviation of noise in the pixels surrounding the peak is proportional to the standard deviation of the noise in an intensity correlation image acquired in the same condi- [55] shows that the SNR varies as 1{xI cl y.…”
Section: Details About the Quantum Holographic Measurements Performed In The Presence Of Static And Dynamic Stray Lightmentioning
confidence: 96%
“…For a fixed exposure time and pump power, the SNR varies as ? N , where N is the number of images used to reconstruct the intensity correlation images [55]. In the presence of stray light, the SNR decreases as 1{xI cl y, where xI cl y is the average intensity of classical light falling on the sensor [31,32].…”
Section: Phase Distortion Characterisationmentioning
confidence: 99%
See 1 more Smart Citation
“…As detailed in the 'Methods' section, σ is calculated from the standard deviation of the noise surrounding the coincidence peaks in the sum-and minus-coordinate projections of the JPD. For a fixed exposure time and a constant source intensity, σ depends only on the number of frames acquired to compute the JPD 43 . Figure 4a shows that the measured values of C for different total number of frames N (black crosses) are found to scale as ffiffiffi ffi N p (blue dashed curve, see 'Methods').…”
Section: Confidence Level Analysismentioning
confidence: 99%
“…(13) to show that σ ∝ Σ. Finally, we use the fact that Reichert et al 43 have shown that Σ / 1= ffiffiffi ffi N p for a constant average pump power and a fixed exposure time. Thus, we conclude that C / ffiffiffi ffi N p : As shown in Fig.…”
Section: Variation Of the Confidence Level C With The Number Of Images Nmentioning
confidence: 99%